Imiquimod-induced ROS production disrupts the balance of mitochondrial dynamics and increases mitophagy in skin cancer cells. Issue 3 (June 2020) - Chuang, Kai-Cheng; Chang, Chuang-Rung; Chang, Shu-Hao; Huang, Shi-Wei; Chuang, Show-Mei; Li, Zheng-Yi; Wang, Sin-Ting; Kao, Jun-Kai; Chen, Yi-Ju; Shieh, Jeng-Jer
Highlights: Imiquimod induces robust ROS production and cause mitochondrial dysfunction. Imiquimod undermines mitochondrial dynamics and causes mitochondrial fission. Imiquimod induces mitophagy. Diminishing imiquimod-induced ROS reduces mitochondrial fission and mitophagy. Abstract: Background: Mitochondrial homeostasis is a highly dynamic process involving continuous fission and fusion cycles and mitophagy to maintain mitochondrial functionality. Imiquimod (IMQ), a Toll-like receptor (TLR) 7 ligand, is used to treat various skin malignancies. IMQ also induces apoptotic and autophagic cell death in various cancers through a TLR7-independent pathway. Objective: To investigate whether IMQ-induced ROS production is involved in mitochondrial dysfunction, mitochondrial fragmentation and mitophagy in skin cancer cells. Methods: BCC/KMC-1, B16F10 and A375 skin cancer cells, AGS gastric cancer cells and primary human keratinocytes were treated with 50 μg/mL IMQ. After 4 h, ROS were detected by CM-H2 DCFDA, DHE, and MitoSOX Red staining. After 24 h, cell viability and the mitochondrial membrane potential were evaluated by a CCK-8 assay and JC-1 staining, respectively. Oxygen consumption was assessed with an Oroboros instrument. Mitochondrial morphology and mitophagy were evaluated by MitoTracker and LysoTracker staining. Mitochondrial dynamics markers, including MFN-1, DRP-1 and OPA1, and mitophagy markers, including LC3, S65-phosphorylated ubiquitin, PINK1 and TOM20, were detected by immunoblotting. Results: IMQ not only induced severe ROS production but also resulted in increased mitochondrial membrane potential loss, mitochondrial fission and mitophagy and decreased oxygen consumption in skin cancer cells compared with normal keratinocytes. Pretreatment with the antioxidant NAC reduced IMQ-induced ROS production and attenuated IMQ-induced mitochondrial fission and mitophagy in skin cancer cells. Conclusions: IMQ-induced ROS might be associated with mitochondrial dysfunction, mitochondrial fission and mitophagy in cancer cells. Alleviating IMQ-induced ROS production would reduce mitochondrial fission-to-fusion skewing and further reduce IMQ-induced mitophagy.